A Survey on Information Flow Monitoring System Using Skyline Algorithm - Jyothsna Priya, K.M; Srinivasulu, A (International Journal of Computer Sciences and Engineering, 2025)
ocial media are websites and computer programs that enable users to create and share information on the internet using a computer or a mobile phone. Large quantities of data are generated by social networks in seconds. The information which is generated in a social network is transformed into a flow by the subjects who produce, transmit, and consume it. This flow can be represented as a very complicated directional graph. In this graph each subject is represented as a node, and the flow of information is represented as a directed edge. In this paper, we introduce a method of dividing this complex directional graph by user and quantifying the flow of information between and among users based on information flow vectors. We propose a system that can monitor the flow of information in social networks using information flow vectors extracted from social media data. We also introduce an improved skyline algorithm that can respond quickly to a user‘s various queries.